Refleksi Perempuan Arab Modern dalam Film Barakah Yuqobil Barakah - Ifi Erwhintiana; Aning Ayu Kusumawati (Center of Language and Cultural Studies, 2021)
This study aims to reveal the portrait of modern Arab women in the film Barakah Yuqobil Barakah, as well as to explain the discourse of modernity in Saudi Arabia based on Pierce's perspective. This research is a qualitative descriptive study. The data collection technique used was the observation and note technique. Researchers used descriptive analysis techniques based on Miles and Huberman's models, namely; data reduction, data presentation, and conclusions. The results showed that the icons, indexes, and symbols related to the modern portrait of Saudi Arabian women. The icons that appear are social media as a reflection of technological progress, and the ideal(body-body goals) as a reflection of modern women. Meanwhile, the index that appears is the Karakoza brand as a reflection of independent and modern entrepreneurial freedom. The symbols that appear are the open style of clothing, Brand ambassadors, and celebrities which are symbols of modernity experienced by aunts as Arab women. Within the frame of the media, film as a cybertext becomes a value-free space for readers to construct discourses conveyed by the authors.